Reconsidering the Relationship between Worship, Spiritual Formation, and Politics through the History and Practice of Korean Hymnody - Kim, Jonghyun (Liturgy, 2025)
This article examines the close relationship between worship, spiritual formation, and politics through the history and practice of Korean Protestant hymnody. While politics, as the realm of public issues, may seem distinct from worship, it is essential to recognize that Christian worship does not exist in isolation from the world. Historically, Korean Protestant hymnody has played a significant role in shaping spiritual formation within the context of political turmoil. This phenomenon is not limited to early Korean Christianity; it remains relevant today, as our society is far from perfect. In this light, I argue for a broader understanding of Christian worship that engages with the real world.